The Green Marble : Earth System Science and Global Sustainability - Turner, David (Columbia University Press, 2018)
Humans have difficulty thinking at the global scale. Yet as we come to understand our planet as a single, interconnected, complex system and encounter compelling evidence of human impact on Earth's climate and biosphere, the need for a truly global effort is increasingly urgent. In this concise and accessible text, David P. Turner presents an overview of global environmental change and a synthesis of research and ideas from the rapidly evolving fields of earth system science and sustainability science that is suitable for anyone interested in humanity's current predicaments and what we can do about them.The Green Marble examines Earth's past, contemporary human disruption, and the prospects for global environmental governance. Turner emphasizes the functioning of the biosphere-the totality of life on Earth-including its influence on geologic history, its sensitivity to human impacts, and its possible role in ameliorating climate change. Relying on models of the earth system that synthesize vast amounts of monitoring information and recent research on biophysical processes, The Green Marble describes a range of scenarios for our planetary home, exploring the effects of anthropogenic greenhouse gas emissions and factors such as economic globalization. Turner juxtaposes cutting-edge ideas from both the geosciences and the social sciences to illustrate how humanity has arrived upon its current dangerous trajectory, and how we might pull back from the brink of civilization-challenging environmental change. Growing out of the author's popular course on global environmental change, The Green Marble is accessible to non-science majors and provides a framework for understanding the complex relationship of humanity to the global environment.